Malaria and other febrile diseases among travellers: the experience of a reference centre located outside the Brazilian Amazon Region - Dotrário, Andréa Beltrami; Menon, Lucas José Bazzo; Bollela, Valdes Roberto; Martinez, Roberto; de Almeida e Araújo, Daniel Cardoso; da Fonseca, Benedito Antônio Lopes; Santana, Rodrigo de C. (Malaria journal, 2016)
Background Malaria is endemic in countries located in tropical and sub-tropical regions. The increasing flow of domestic and international travellers has made malaria a relevant health problem even in non-endemic regions. Malaria has been described as the main diagnosis among travellers presenting febrile diseases after returning from tropical countries. In Brazil, malaria transmission occurs mainly in the Amazon region. Outside this area, malaria transmission is of low magnitude. Methods This cross-sectional study aimed to describe the experience in the diagnosis of malaria in a reference centre located outside the Brazilian Amazon Region, emphasizing the differences in clinical and laboratory markers between cases of malaria and those of other febrile diseases (OFD). Medical charts from adult patients (≥18 years) who underwent a thick smear test (TST) for malaria, between January 2001 and December 2014, were retrospectively reviewed. Results A total of 458 cases referred to perform the TST were included. Malaria was diagnosed in 193 (42 %) episodes. The remaining 265 episodes (58 %) were grouped as OFD. The majority of malaria episodes were acquired in the Brazilian Amazon Region. The median time between the onset of symptoms and the TST was 7 days. Only 53 (11.5 %) episodes were tested within the first 48 h after symptom onset. Comparing malaria with OFD, jaundice, nausea, vomiting, and reports of fever were more prevalent in the malaria group. Low platelet count and elevated bilirubin levels were also related to the diagnosis of malaria. Conclusions The results indicate that outside the endemic area travellers presenting febrile disease suspected of being malaria underwent diagnostic test after considerable delay. The reporting of fever combined with a recent visit to an endemic area should promptly evoke the hypothesis of malaria. In these cases, specific diagnostic tests for malaria should be a priority. For cases that jump this step, the presence of elevated bilirubin or thrombocytopaenia should also indicate a diagnosis of malaria.